A transformação digital no Instituto Federal de Mato Grosso do Sul: um estudo à luz da Teoria Institucional - Gabriele de Arruda Cardoso (2021)
The uncertainty scenario produced by the Covid-19 pandemic raised information and communication technologies to a leading role that highlighted challenges for organizational activities in the year 2020. In Brazil, the digital transformation efforts in the public sector date back two decades, being the most recent instruments the publication of the Digital Governance Strategy (2016) and the Digital Government Strategy (2020). According to the Organization for Economic Cooperation and Development, one of the main challenges that governments confronts when implementing digital government policies refers to the development of integrated and coherent efforts in the public sector. In this sense, the Federal Institute of Mato Grosso do Sul (IFMS), as a member of the Federal Public Administration and a reference in technological education, plays an important role in achieving the governmental goals of digital transformation. Therefore, the general objective of this study was to propose an action plan aimed at improving the institution's technological management processes. For this purpose, the specific objectives were identified as digital technologies implemented in this educational organization between the years 2016 and 2020; identify the isomorphic mechanisms present in this process; and analysis of the current stage of institutionalization of digital transformation in the IFMS. This research, therefore, it is characterized as qualitative, descriptive-exploratory. For data collection, we performed the techniques of document research, interview and application of an electronic questionnaire. To interpret the data obtained, the technique called Pattern Matching, by Trochim (1989) was applied. Data analysis allowed us to conclude that the digital transformation process at the IFMS is in the habitualization stage, that is, pre-institutionalization, but with elements strongly directed to the objectification stage. Elements of coercive, mimetic and normative isomorphisms were also identified, as well as opportunities to improve technological management within the institution scope study.